Ability to Tolerate Acidity, Resist and Absorb Aluminum of Fungi Isolated from Tea Soils in Tan Cuong, Thai Nguyen, Vietnam - Thi Tuong Chau, Ngo; Thi Mai Luong, Nguyen; Thi Ngoc Mai, Phung; Van Huy, Dao; Van Thien, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4319, 2018)
Abstract: From tea soils in Tan Cuong (Thai Nguyen, Vietnam), 16 acid- tolerant and aluminum- resistant fungi were isolated on Hansen plates (pH 3.0) with 100 mgL -1 Al. Two strains (F8 and F13) could grow wellon Hansen plates (pH 3.0) with 700 mgL -1 Al. Morphological and 28S rDNA sequence analyses indicated that strain F8 belonged to Eupenicillium javanicum , while strain F13 belonged to Penicillium variabile . Further investigation showed that both strains could grow actively in Hansen broth with 100 mgL -1 Al at pH 2.2- 5.0 and with 500- 2,000 mgL -1 Al at pH 2.4. After 7 days of incubation on a shaker at 30 o C, 150 rpm, the aluminium absorption efficiency from Hansen broth with 2000 mgL -1 Al (pH 2.4) of strain F8 was 92.06% and that of strain F13 was 86.88%. The fungi areconsidered to be useful not only to improve acidified soils by decreasing the ionic aluminum concentration but also ensure quality of tea product. Keywords: Acid soil, tea soil, acid-tolerant fungi, aluminum-resistant fungi, aluminium absorption. References [1] M. Hayatsu, Soil microflora and microbial activities in acid tea soils,Bull. Natl. Res. Veg. Ornam. Plants Tea B 6 (1993) 73 (in Japanese). [2] Nioh, T. Isobe, M. Osada, Microbial biomass and some characteristics of a strongly acid tea field soil, Soil Sci. Plant Nutr. 39 (1993) 617-625. [3] H Wang, R.K. Xu, N. Wang, X.H. Li, Soil acidification of Alfisols as influenced by tea cultivation in eastern China,Pedosphere 20(6) (2010) 799- 806. [4] M.L. Jackson, P.M. Huang, Aluminum of acid soils in the food chain and senility, Sci. Total Environ. 28(1) (1983) 269-276. [5] J. Edwardson, Aluminum and the pathogenesis of neurodegenerative disorders, Aluminium Food Environ. 2 (1988) 20-36. [6] C.N. Martyn, Aluminium and Alzheimer's disease: an epidemiological approach, Environ Geochem. Health 12(1-2) (1990) 169-171. [7] D. McLachlan, Aluminium and the risk for Alzheimer's disease, Environmetrics 6(3) (1995) 233-275. [8] P. Illmer, K. Marschall, F. Schinner, Influence of available aluminum on soil-microorganisms, Lett. Appl. Microbiol. 21(1995)393-397. [9] F. Kawai, D. Zhang, M. Sugimoto M, Isolation and charac- terization of acid-and Al-tolerant microorganisms. FEMS Microbiol. Lett. 189 (2000) 143-147. [10] S. Kanazawa, N.T.T. Chau, S. Miyaki S, Identification and characterization of high acid tolerant and aluminum resistant yeasts isolated from tea soils,Soil Sci. Plant Nutr. 51 (2005) 671-674. [11] N.T.T. Chau, L.V. Thien, S. Kanazawa, Identification and characterization of acidity-tolerant and aluminum-resistant bacterium isolated from tea soil, African Journal of Biotechnology 13(27) (2014) 2715-2726. [12] G. He, X. Wang, G. Liao, S. Huang,J. Wu, Isolation, Identification and characterization of two aluminum- tolerant fungi from acidic red soil, Indian J. Microbiol. 56(3) (2016) 344-352. [13] S.Kanazawa, T. Kunito T, Preparation of pH 3.0 agar plate, enumeration of acid-tolerant and Al-resistant microor- ganisms in acid soils, Soil Sci.Plant Nutr. 42 (1996) 165-173. [14] A.K.N.Zoysa, A. Anandacoomaraswamy, M.S.D.L.De Silva, Management of soil Fertility in tea lands, Handbook on tea, Tea research institute of Sri Lanka, 2008; pp 27-33.